Feasibility of an Internet-based positive psychological intervention for hemodialysis patients with symptoms of depression. (26th November 2018) - Hernandez, Rosalba; Burrows, Brett; Wilund, Kenneth; Cohn, Michael; Xu, Shuo; Moskowitz, Judith T.
ABSTRACT: Background : Depression is a pervasive psychological issue facing hemodialysis (HD ) patients. Novel technology-based treatment strategies that deploy psychology-based interventions have not been the focus for therapy and few published studies exist. The aim of the current trial is to determine the feasibility and acceptability of an Internet-based positive psychological intervention in HD patients with comorbid depressive symptoms.Methods : HD patients (n = 14) with elevated symptoms of depression were enrolled in a single-arm pre-post trial with clinical assessments at baseline and immediately post intervention. Chairside during regularly scheduled HD treatment, patients utilized a web browser to complete online modules promoting skills for increasing positive emotion over a 5-week period using Apple IPads. Targeted skills included noting of daily positive events, gratitude, positive reappraisal, acts of kindness, and mindfulness/meditation.Results : Twelve of 14 patients completed the program for an 85.7% retention rate. Participants felt satisfied with each session and offered consistently positive feedback. On average, participants visited the website 3.5 times per week. Significant improvements were evident for depressive symptoms (15.3 vs. 10.9; p  = 0.04), as per the Center for Epidemiological Studies Depression Scale.Conclusions : An innovative Internet-based positive psychological intervention represents a feasible and useful therapeutic option for HD patients with depressive symptoms.